WOUND HEALING EFFECT OF POLYHEXAMETHYLENE GUANIDINE HYDROCHLORIDE HYDROGELAT BURNS - S. N. Lebedeva; O. S. Ochirov; S. A. Stelmakh; M. N. Grigoryeva; S. D. Zhamsaranova; D. M. Mognonov (Acta Biomedica Scientifica, 2017)
This article considers the wound-healing effect of a hydrogel based on polyhexamethyleneguanidine hydrochloride under conditions of thermal shock modeling. The presence of gelling properties in combination with the high biocidal activity of polyguanidins opens the prospect of obtaining an effective single-component external agent, which is very important for antimicrobial chemotherapy of wounds and burns, as in their treatment there is a high probability of infecting the wound with microorganisms causing various infectious diseases. Previously, we developed a method for the preparation of a hydrogel based on polyhexamethyleneguanidine hydrochloride, which involves the cross-linking of the amino-end groups of the branched polymer with formaldehyde, resulting in a cross-linked polymer, which is a lump-like mass. The mechanical treatment of the hydrogel makes it possible to give the material an ointment form that is convenient for application to the skin. An experiment on the evaluation of the wound healing action of hydrogel was carried out under the conditions of modeling a thermal burn. The comparative preparation was multicomponent gel "Levomekol", in which polyethylene oxide was used as the basis. It was established that the hydrogel activates the growth of antioxidants and leukocytes in the blood of animals in dynamics on the 10th, 17th and 24th day of the experiment, amounting to 56.4 %, 33.8 % and 20.9 %, and of leukocytes - 27.7 %, 19.6 %; 6,2 % in relation to the norm. The method of contrast radiography of penetrating wounds showed that the daily reduction in the wound area is most pronounced in the hydrogel group, which indicates a pronounced reparative effect.